Teaching Staff of Industrial Engineering of Sultan Ageng Tirtayasa University - ulfah, maria (Fakultas Teknik Jurusan Teknik Industri Universitas Sultan Ageng Tirtayasa, 2016)
Nowadays refined sugar supply chain is often occured risk (disruption)that the complained by food industry, beverage and pharmaceutical industries as consumer of refined sugar. The purpose of this research is to design a risk management model of refined sugar supply chain and realized in the framework of risk mitigation actions.The method used in the identification and evaluation constitute development of method Failure Modes and Effect Analysis (FMEA) and Quality Function Deployment (QFD), while the determination of the criteria in the process business was using Supply Chain Operation Reference (SCOR) dimension. Of the research methods used will be developed a formulation the value potential risks for determining priority risks agent will be mitigated by the approach House of Risk (HOR).HOR1 is used to rank each risk agent based on their aggregate risk potentials. HOR2 is intended to prioritize the proactive actions that the company should pursue to maximize the cost-effectiveness of the effort in dealing with the selected risk agents in HOR1. The results of the HOR model was to handle 24 risk agent by implementing 22 risk mitigation actions.